2016
DOI: 10.1074/jbc.m115.701102
|View full text |Cite
|
Sign up to set email alerts
|

The Activation Mechanism of Glycoprotein Hormone Receptors with Implications in the Cause and Therapy of Endocrine Diseases

Abstract: Glycoprotein hormones (GPHs) are the main regulators of the pituitary-thyroid and pituitary-gonadal axes. Selective interaction between GPHs and their cognate G protein-coupled receptors ensure specificity in GPH signaling. The mechanisms of how these hormones activate glycoprotein hormone receptors (GPHRs) or how mutations and autoantibodies can alter receptor function were unclear. Based on the hypothesis that GPHRs contain an internal agonist, we systematically screened peptide libraries derived from the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 62 publications
(61 reference statements)
3
68
0
Order By: Relevance
“…The FSHR ECD structure reported by Jiang and colleagues ( 7 ), identified the hinge region as an integral part of the ECD (Figure 1B ), and confirmed previously reported biochemical data on the FSHR and TSHR ( 85 , 90 93 ), underlying the role of this region in ligand-stimulated receptor activation. These and other studies ( 94 ) have also suggested that the ECD of the glycoprotein hormone receptors acts as a tethered inverse agonist. In this scenario, the ECD acts as an agonist upon ligand binding and activates the sequence 353FNPCEDIMGY362 located in the junction of the carboxyl-terminal end of the hinge region and the 7TMD helix 1, which function as an internal agonist unit (Figure 1B ).…”
Section: Fshr Domains Involved In Ligand Binding and Receptor Activatsupporting
confidence: 52%
“…The FSHR ECD structure reported by Jiang and colleagues ( 7 ), identified the hinge region as an integral part of the ECD (Figure 1B ), and confirmed previously reported biochemical data on the FSHR and TSHR ( 85 , 90 93 ), underlying the role of this region in ligand-stimulated receptor activation. These and other studies ( 94 ) have also suggested that the ECD of the glycoprotein hormone receptors acts as a tethered inverse agonist. In this scenario, the ECD acts as an agonist upon ligand binding and activates the sequence 353FNPCEDIMGY362 located in the junction of the carboxyl-terminal end of the hinge region and the 7TMD helix 1, which function as an internal agonist unit (Figure 1B ).…”
Section: Fshr Domains Involved In Ligand Binding and Receptor Activatsupporting
confidence: 52%
“…FSH binding to its cognate receptor, the FSHR, leads to the rewiring of a complex intracellular signaling network that profoundly alters gene regulation at several levels. Hormone binding to the Leucine-rich repeat domain provokes conformational changes in the receptor, including the interaction of a sulfated tyrosine within the receptor hinge region with the interface of FSH α and β chains [4,5], and tethering of a decapeptide that protrudes out of the plasma membrane from the first intracellular transmembrane helix [6]. Work is still ongoing to decipher the crystal structure of the entire FSHR, including transmembrane domains, in active conformation.…”
Section: Fsh-induced Signaling Networkmentioning
confidence: 99%
“…After having already been shown for the LHR in 1999 that a short extracellular sequence near transmembrane helix (TMH) 1 is important for hormone mediated signaling [24], later it was suggested that the intramolecular agonistic unit in TSHR comprises specific amino acids localized immediately prior TMH1 [25] and further experiments refined these insights [26,27]. This was greatly confirmed by a recent peptide screening study that revealed a decapeptide representing a highly conserved sequence shortly prior TMH1 in GPHR as a tethered "internal agonist" [28]. Homology models suggest that this internal agonistic sequence in the hinge region's C-terminus (assumed for all three GPHR subtypes) is i) covalently connected to a short helix (converging helix) in the N-terminus of the hinge region via a disulfide bridge (Cys408-Cys284 in TSHR), ii) located at the transition to TMH1 and is iii) con-sequently embedded in between the extracellular loops of the seven TMHs (reviewed in [29]).…”
Section: Internal Agonistmentioning
confidence: 86%
“…The internal tethered agonist in the GPHR can obviously also be targeted, which has been shown by adding the sequence of the internal agonist to the receptor as peptide. The peptide FNPCEDIMGY activates non-specifically TSHR and also LHR and FSHR, whereas its mutant peptide FNPCKDIMGY acts as unspecific inhibitor [28]. Both suggest that these peptides directly affect the tethered agonist.…”
Section: Allosteric Modulationmentioning
confidence: 99%
See 1 more Smart Citation